Reduced Neuromuscular Performance in Night Shift Orthopedic Nurses: New Insights From a Combined Electromyographic and Force Signals Approach - Cè, Emiliano; Doria, Christian; Roveda, Eliana; Montaruli, Angela; Galasso, Letizia; Castelli, Lucia; Mulè, Antonino; Longo, Stefano; Coratella, Giuseppe; D’Aloia, Pasqualino; Banfi, Giuseppe; Esposito, Fabio (Frontiers in Physiology, 2020)
The effect of sleep–wake rhythm disruption on neuromuscular control and muscle fatigue has received little attention. Because nurse shift work is so varied, including overnight duty, rotating shift schedules, early awakening, and interrupted nocturnal sleep, it offers an interesting model to study this paradigm. It has been investigated so far using only subjective markers. A combined approach based on the simultaneous analysis of surface electromyographic (sEMG) and force signals can objectively detect possible deficits in neuromuscular control and muscle fatigue. With this study we investigated neuromuscular activation and muscle contraction capacity at submaximum and maximum level in nurses working two night-shift schedules and compared them to levels in nurses working entirely in day shifts. Sleep quality and activity levels were also assessed. The study sample was 71 nurses grouped by their shift work schedule: night shift for 5 days (NS5, n=46), night shift for 10 days (NS10, n=9), and only day/swing shift (DS, n=16). Before and after the shift-work cycle, maximum voluntary contraction (MVC) force and muscle activation, neuromuscular control, and muscle fatigability were measured in the finger flexor muscles. Activity level and sleep quality during the shift-work cycle were recorded with a wrist actigraph. After the shift-work cycles, MVC force and muscle activation were decreased (-11±3% and -33±3%, p<0.001) as was neuromuscular control (-36±8%, p=0.007), whereas muscle fatigability was increased (+19±9%, p=0.006) in the NS5 and the NS10 group. Sleep quality was lower in the NS5 and the NS10 group (-8±1.8% and -15%3, respectively, p<0.001), while the activity level for the three groups was similar. There was a clear reduction in neuromuscular control and an increase in muscle fatigue in the nurses working the night shift. These findings may inform of work schedule planning or recommendations for devising new recovery strategies to counteract neuromuscular alterations in night shift nurses.